Design Of Information Systems On a Official Travel at PT Perkebunan Nusantara XII (Persero) Surabaya - Safi'i, Imam; Sudarmaningtyas, Pantjawati; Rahmawati, Endra (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT Perkebunan Nusantara XII (Persero) or called PTPN XII is government enterprise that focused on agri-bussines and agri-industy sector. PTPN XII have 34 garden in East Java, 3 regional office and 5 subsidiary enterprise. Employees who will visit regional office, garden or subsidiary enterprise have to do a official travel. Based on currently business process of official travel, there are a few problem such as misuse official travel for personal interest, tardiness of getting business document, miscalculation official travel fee, and there are no report to reviewing the use of cost. Build a official travel information system is need to resolve currently problem. This system can generate employee official travel history, sorting by priority to create official travel document, give a reminder for create document official travel, automation calculation official travel fee, integrated with budget and create the use of cost official travel report. After testing and evaluatin of system, all function of system is working properly. So official travel information system can resolve the existing problem with all function which it have.